A Pragma-Logical Analysis of Manipulation Strategies Used by American and Arabic Attorneys in Selected Criminal Trials - Dahaam, Ziyad Ahmed; Salih , Ahmed Mohammed (Journal of Ecohumanism, 2024)
This study is devoted to investigate the defense of American and Arabic attorneys from a pragma-logical perspective. It is hypothesized that manipulation is a dangerous pragmatic act which is practised by them when defending their clients in criminal trials. Therefore, this study aims to prove that their defense contains arguments which do not agree with the proof standard of criminal cases. Such a proof requires them to present logical evidences beyond a reasonable doubt to persuade the members of the jury that their clients are innocent, or at least they have logical reasons which led them to commit their murders. To achieve the aims of the study, six arguments are chosen for analysis. The first three are advanced by the American defense attorney Robert Rogers. The next three are advanced by the Arabic defense attorney Mustafa Ramadan. Their defense is analyzed qualitatively and tested according to the pragma-logical criteria discussed below. The results show that they both resort to different argumentation schemes, different logical components, and different logical fallacies. These differences indicate that their arguments are fallacious and serve a pragmatic manipulative intention.